ISO 37001: Anti-Bribery Management System-Benefits and Implementation - Nurul Khair, Ishak; Hasnah, Haron; Ishak, Ismail; Siti Zabedah, Saidin (Universiti Malaysia Pahang, 2017)
Anti-Bribery Management System was first introduced in Malaysia in 15th October 2016. Before this, other countries such as United Kingdom and the United States have come out with the act. The UK Bribery Act, 2010 was passed on 8 April 2010 and was enforced on 1 July 2011 and the US Foreign Corrupt Practices Act, was enacted in 1977 and was amended in 1988. This paper will discuss the purpose of ISO 37001, what an organization should have to implement the system and what are the benefits that can be gained from the implementation.